Efectos del silicio sobre el crecimiento y canalización de biomasa en chusquines de Guadua angustifolia Kunth (2012)
With the aim of assessing some ecophysiological responses in Guadua angustifolia at varying concentrations of soil silicon, a total of 110 seedlings were grown during eight months in conditions of controlled nursery irrigation. The seedlings were planted in polyethylene bags (1.2 L-volume), where the soil was enriched with silicon in the form of commercial fertilized pellets (75% SiO2), in 11 treatments in which the silicon concentrations increased every 600 mg, from 0 mg to 6000 mg. Total seedling biomass, leaf and root biomass, leaf area and stem height were all significantly (p<0.05) affected by the soil silicon. Overall, multiple comparisons of treatments after anovas for these variables revealed two groups of treatments. In the first group the control treatment was not significantly different (p>0.05) from each of the low to middle concentration treatments (600 mg to1200 mg Si). In the second group the control was significantly (p<0.05) different from the middle to high concentration treatments (2400 a 6000 mg Si), with no differences within each of these two groups and the highest of the first group compared to the lowest of the second group.